Listening to Women’s Letters - Ahrendt, Rebekah; van der Linden, David (Early Modern Low Countries, 2025)
This article analyses the letter-writing practices of women, focusing on a single letter written at the turn of the eighteenth century by a woman in Paris to an opera director in The Hague. Our case study shows we have much to gain from letters written by women further down the social hierarchy, as most scholarship has focused on the elite. By reading between the lines and employing responsible speculation, historians can gain insight into the challenges and opportunities available to working women on the move, such as performers. Learning to read these letters differently – learning to truly listen to them – enables us to achieve new understanding of the ways in which women created and sustained relationships through correspondence.